Red Wine: Poison or the Secret to Eternal Youth? - Makowska, Karolina; Lis, Laura; Perwejnis, Sebastian (Quality in Sport, 2024)
Red wine has been the subject of extensive research due to its complex polyphenolic composition and potential health effects on the human body. This review examines the cardioprotective effects of red wine, highlighting the role of polyphenols in promoting cardiovascular health, increasing insulin sensitivity, and offering protective benefits against type 2 diabetes and neurodegenerative diseases. Despite these potential benefits, red wine consumption is also associated with several adverse effects, including liver damage, headaches, and increased risk of depression. This duality highlights the importance of moderation in alcohol consumption..